2014
DOI: 10.1080/15435075.2014.889001
|View full text |Cite
|
Sign up to set email alerts
|

The System Dynamics of Nuclear Energy in Singapore

Abstract: In this article, a system dynamics model is developed to study the complex issues involving nuclear energy in Singapore by assessing four essential aspects, namely (1) Economic, (2) Environment, (3) Social, and (4) Political in various scenarios. The first factor juxtaposes the monetary benefit from deploying nuclear energy with the current situation. The second deals with carbon dioxide emission, nuclear waste, and thermal pollution from nuclear power plant. The third part discusses the safety and social acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…System dynamics offers a holistic approach, taking into account the uncertainties, time delays, and feedbacks of a system, facilitating better systems understanding for developing energy policy development [21]. Research in different areas of energy systems were suggested, such as energy behavior [22], social acceptance [23], economic costs [24], network and infrastructure issues, innovation, security and reliability, markets, and governance issues [25]. In Finland, energy security alternative sources were studied in order to see how renewables, fossil fuels, and nuclear can contribute in reducing dependency on external energy sources [26].…”
Section: Previous Work On Systems Thinking In Electric Power Generationmentioning
confidence: 99%
“…System dynamics offers a holistic approach, taking into account the uncertainties, time delays, and feedbacks of a system, facilitating better systems understanding for developing energy policy development [21]. Research in different areas of energy systems were suggested, such as energy behavior [22], social acceptance [23], economic costs [24], network and infrastructure issues, innovation, security and reliability, markets, and governance issues [25]. In Finland, energy security alternative sources were studied in order to see how renewables, fossil fuels, and nuclear can contribute in reducing dependency on external energy sources [26].…”
Section: Previous Work On Systems Thinking In Electric Power Generationmentioning
confidence: 99%
“…Bodger showed that the SD model was also applicable to a small country where specific energy resources are available [20]. Chia et al developed a system dynamics model to study the complex issues involving nuclear energy development in Singapore by evaluating four critical aspects, namely environmental, economic, political and social factors in various scenarios [21]. The SD modeling approach can be used to systematically model the oil and gas industry, and to conduct a scenario analysis and uncertainty analysis according to possible changes [22][23][24].…”
Section: State Of Literaturementioning
confidence: 99%
“…Sterman was involved in the conversion of FOSSIL1 to FOSSIL2, a model that includes feedback from within the economy and energy system [16,17]. The SD modelling approach is very popular in literature on the energy sector and it has also been applied to many countries, such as the United States, UK, Argentine and so on [18][19][20][21]. Based on the life cycle of the petroleum resource, Davidsen et al presented an SD model to show the interactions and feedback process of the petroleum industry in the United States [18].…”
Section: State Of Literaturementioning
confidence: 99%